2020
DOI: 10.33902/jpsp.2020263901
|View full text |Cite
|
Sign up to set email alerts
|

Possible impact of COVID-19 on senior secondary school students performance in science education in Nigeria

Abstract: The recent outbreak of Coronavirus (COVID-19) pandemic has led to the total lockdown of major cities globally which resulted in the early closure of schools in the cities affected, Nigeria inclusive. It is hypothesized that COVID-19 may have a negative outcome on the performance of senior secondary school students in class 3 (SS3) who are yet to write their 2020 external examination (West Africa Senior Secondary Certificate Examination as well as National Examination Council) especially in the science subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
4
12
0
4
Order By: Relevance
“…Furthermore, the findings of a study conducted by Sintema (2020) support the result of the present study indicating that COVID-19 affected the examination result of the students. Similarly, other studies conducted by (Mahdy, 2020a;Oyinloye, 2020) confirming that COVID-19 has negatively affected the education system of Nigeria, particularly the performance of students. In addition, this finding is similar to the studies reviewed on the literature indicating that COVID-19 affected the academic performance of students.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the findings of a study conducted by Sintema (2020) support the result of the present study indicating that COVID-19 affected the examination result of the students. Similarly, other studies conducted by (Mahdy, 2020a;Oyinloye, 2020) confirming that COVID-19 has negatively affected the education system of Nigeria, particularly the performance of students. In addition, this finding is similar to the studies reviewed on the literature indicating that COVID-19 affected the academic performance of students.…”
Section: Discussionsupporting
confidence: 62%
“…Although not many studies have been done exploring the effects of COVID-19 on the academic performance of students and assessing their level of satisfaction with online teaching during the outbreak of COVID-19, but the researcher made an effort to find out the most related studies concerning the present study. Regrettably, the outbreak of COVID-19 affected greatly almost all the educational levels in different contexts across the globe and have been incorporated into the educational settings to have possible provision for teachers and students (Oyinloye, 2020). A study conducted by Gonzalez, Rubia, et al (2020) examined the impacts of COVID-19 confinement on the performance of students at the higher education level.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…In this study, low school performance and school suspension predicted lower compliance with COVID-19 regulations. Previously, a study found that changes in the process of teaching and learning during the pandemic were related to a decreased school performance (Oyinloye, 2020), and low school performance was found to be related to more antisocial behaviors (Farrington, 2005). Academic performance in students is affected by inequalities in educational requirements (Ogbu & Simons, 1998), and online education during the pandemic could increase this gap (Engzell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, teachers can influence student compliance and academic behaviors (Matheson & Shriver, 2005) and, at the same time, teacher-student relationships are a protective factor against antisocial behaviors (Obsuth et al, 2021). Changes in teaching and learning strategies during the pandemic were related to decreased school performance (Oyinloye, 2020). It is possible that students with low school performance and problem behavior at school complied less with COVID-19 regulations.…”
Section: Cumplimiento De Medidas Covid-19 En Adolescentes Y Variables...mentioning
confidence: 99%
“…Most of the numerous research studies reviewed investigated the effect of Covid-19 on students' academic performance while others looked at students' involvement or participation in extracurricular activities and student's overall performance in learning. Oyinloye (2020), Agbele and Oyelade (2020), Osman (2020), Hubert and Helm (2020), Adelakun (2020) and Ogunode (2020) have conducted various studies on the impact of Covid-19 on education system, schooling and its influence on students' academic performance at secondary school level without investigating its influences on school activities and how stakeholders perceive these influences. Also, Jelinska and Paradowski (2021) conducted research on teachers' perception of student coping with emergency remote instruction during Covid-19 pandemic while Sibanda and Mathwasa (2021) conducted their research on the perceptions of teachers and learners on the impact of Covid-school female learners.…”
Section: Introductionmentioning
confidence: 99%